Live Shopping Dalam Perspektif Syariah: Analisis Kualitatif Terhadap Indikasi Gharar Dan Preferensi Konsumen - Findartika, Lusianah Dhewi; Handayani, Iin Sri; Honainah; Qomariyah , Lailatul; Fauzi, Mohammad; Iman, Aldi Khusmufa Nur (CV. SINAR HOWUHOWU, 2025)
Amid the growing popularity of buying and selling through live shopping features, this phenomenon has gained significant attention, particularly due to the real-time interaction between sellers and consumers. This study aims to analyze the indications of gharar and consumer preferences toward live shopping from a Sharia perspective. The research employs a descriptive qualitative method using a library research approach, drawing on various relevant academic literatures. The findings indicate that gharar may still occur in live shopping transactions when product specifications are not clearly conveyed. However, the potential for gharar can be minimized through the application of transparency principles in accordance with Sharia values. These include providing clear and accurate product descriptions, implementing firm and easily accessible return policies, and ensuring seller credibility in delivering honest product information. Sellers with high credibility who are able to build responsive and genuine real-time interactions with consumers significantly influence consumer preferences. Furthermore, the interactive nature of live shopping plays a crucial role in shaping consumer preferences, as it not only enhances consumers’ sense of security during transactions but also contributes to sustaining positive consumer preferences in the long term.